Airline Choice Decision for Jakarta-Denpasar Route During the Covid-19 Pandemic - Setiawan, Christoforine Agatha; Belgiawan, Prawira Fajarindra; Dharmowijoyo, Dimas Bayu Endrayana (Journal of the Civil Engineering Forum, 2024)
As one of the most popular destinations in Indonesia, Bali has experienced growth in its domestic passenger arrivals over the last few years. Travel restrictions during COVID-19 have reduced airline passenger numbers on the Jakarta-Denpasar route. The travel restriction has loosened, and the economy is starting to recover in January 2022. However, the number of domestic passengers arriving in Denpasar has not returned to its former state. This research aims to understand the influential factors in the airline decision-making of domestic passengers on the Jakarta-Denpasar route. We started the research with an exploratory study to find the influential factors in which we obtained five attributes. The attributes include airfare, flight schedule, transit number, travel time, and HEPA filter. We conducted a stated choice experiment with five alternatives: Foreign private LCC, Private FSC, Private LCC, Flag LCC, and Flag FSC. The questionnaire was designed with a D-efficient design. We obtained 256 respondents, and there are 2048 observations for the Mixed Multinomial Logit Model estimation. From the estimation, we found that airfare, number of transits, travel time, and HEPA filter are all significant with expected signs. We also found that the flight schedule is not significant. Several socio-demographic variables, such as Gender, Age (except for Flag FSC), and income (also except for Flag FSC), are insignificant in airline choice decisions. We also presented the calculation of elasticity as well as the willingness to pay. Further, we propose that all airlines increase their direct flights for the Jakarta-Denpasar route since respondents prefer less transit. As people are more concerned about public transport’s hygiene, stating that HEPA filters’ availability in airline promotion is also recommended to gain more trust. Finally, our paper offers recommendations for airlines to improve their services and passenger satisfaction after the pandemic recovery period.